Psycho-social health problems: Prevalence and associated factors among students of professional colleges in Jammu - Kumari, Rashmi; Langer, Bhavna; Jandial, Sonia; Gupta, Rajiv Kumar; Raina, Sunil Kumar; Singh, Parveen (Indian Journal of Community Health, 2019)
Background: Psycho-social health problems are an area of concern worldwide especially among students pursuing professional courses. The competition for grades, carrier insecurity often contribute to various emotional disturbances such as stress, anxiety and depression. Aims and Objectives: to determine the prevalence of stress, anxiety and depression in students of two main professional streams (medical & engineering) and to find out various factors associated with them. Material and methods: A cross-sectional study was conducted among students of medical and engineering stream using DASS 42 scale. Further a self administered, pretested questionnaire was used to elucidate information on socio-demographic and personal characteristics. Results: Out of a total of 480 students (300 MBBS and 180 Engineering), prevalence of stress, anxiety and depression in medical & engineering students was 47.6 %, 68.6%, 43.7% and 41.1%, 71.1 % & 40.0 % respectively. On Multiple Regression analysis, relationship with family members emerged as a significant independent predictor for all the three psychogenic factors. Conclusions: A high prevalence of depression, anxiety and stress was found among students of both the streams. There is a need to introduce simple counselling and stress management techniques in curriculum to combat such morbidities